Recurrent optic neuritis: clues from a long-term follow up study of recurrent and bilateral optic neuritis patients - Kurne, Asli; Karabudak, Rana; Yalcin-Cakmakli, Gul; Gursoy-Ozdemir, Yasemin; Aydin, Pinar; Ilksen-Colpak, Ayse; Lule, Sevda; Kansu, Tulay (Eye and brain, 2010)
Optic neuritis (ON) can be recurrent, with unilateral or bilateral presentation. Diagnosis of recurrent cases may be challenging. In this study long-term follow-up of recurrent and/or bilateral ON patients is reported in an effort to guide differential diagnosis and treatment. The study included 474 optic neuropathy patients. Of these, 70 patients with recurrent unilateral or bilateral, and nonrecurrent bilateral ON were assessed. The characteristics of each ON attack, laboratory and magnetic resonance imaging (MRI) findings, associated diseases and response to treatment were noted for each patient. Most of the patients were reevaluated in the outpatient clinic. Seven patients were investigated for neuromyelitis optica (NMO)-immunoglobulin G (IgG) seropositivity. Forty-seven patients had recurrent unilateral ON and 23 had bilateral ON. Mean follow-up was 7.55 years. Final diagnoses for recurrent unilateral group were multiple sclerosis (MS) (n = 29), chronic relapsing inflammatory optic neuritis (CRION) (n = 11), NMO (n = 4), or autoimmune thyroid disease (n = 3); and for bilateral ON group, MS (n = 4), vasculitis (n = 13), postinfectious ON (n = 4), and sarcoidosis (n = 2). Three patients were positive for NMO antibodies. Based on the data collected, we conclude when recurrent ON causes moderate to severe visual loss in the absence of cranial MRI findings typical of MS, other diagnoses should be considered, including NMO.